Development and Psychometric Validation of the Multidimensional Measure of Purpose in Life II (MMOP-II) - Louis Fang; Alfred Allan; Joanne M. Dickson (International Journal of Environmental Research and Public Health, 2026)
Purpose in life is a central motivational construct that has a profound influence on wellbeing. However, existing measures lack the breadth and precision needed to accurately capture this complex construct. In the present study, we aimed to develop a new measure rooted in a holistic, systems-based theoretical framework of purpose in life: the 18-item Multidimensional Measure of Purpose in Life II (MMOP-II). In Study 1, our confirmatory factor analyses in a sample of 303 university students (female = 82.5.%, white = 78.5%) supported a strong five-factor higher-order model fit, outperforming the three-factor and unidimensional alternatives. The Study 2 results replicated these findings in a sample of 290 community adults (female = 54%, white = 76.6%). The results from Study 2 also showed that the MMOP-II correlated with concurrent, convergent, and divergent validity measures in theoretically consistent ways. Across both studies, internal consistency reliability met adequate thresholds for all subscales as well as the total MMOP-II score. Overall, our results support purpose in life as a coherent, higher-order construct measurable by the MMOP-II. Future research should aim to examine the test–retest reliability of the MMOP-II and its generalizability in diverse samples.